(3GdeSGFds - (3GdWHQj , YeQ Hf GdaQNGf GdWHQj, CHhMfaj,J (B200 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg agQS GdCHhGH (B: (3gPG GdcJGH GNJUQg YeQ Hf GdaQNGf GdWHQi ef cJH GdMceGA Ydi CfhGY GdeSGFd hLYdg ChdG jbGS Ydjg GdeSGFd s
(3BNQgG (B:s
(3agh GdOdjd ddQHY hGfXQkG CjVkG GfUGd GdbeQ aGbV YdjgG HNjQ cGf Ch TQ hGddg GYde s
(3ajgG HYV GdQShe GdgfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B304s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B392 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B96 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B165) s
Keywords: (3Gdadcs